Safe use of Dexamethasone in pediatrics: design and evaluation of a novel stable oral suspension - Santoveña-Estévez Ana; Dorta-Vera Diego; González-García Iris; Suárez-González Javier; Teigell-Pérez Nuria; Fariña José B (De Gruyter, 2018)
Dexamethasone is used in pediatrics mainly for treatment of croup and bronchopulmonary dysplasia. Commercially available pediatric oral formulations include inadequate excipients for this population. When there are only commercially available oral dosage forms for adults, a formulation is prepared to reduce the dose by manipulation of authorized tablets or injectable dosage forms. This practice most of times is made without the quality and control that process requires. The aim of this study is to propose a formulation secure and suitable for pediatrics by the use of a Standard Operating Procedure that ensures its quality.